The Role of Political Memes on Social Media in Criticizing Political Policy in the United States 2016-2019 - Halifa Haqqi; Dwi Putro; Andika Murdani (Husnayain Business Review, 2022)
Purpose - This paper seek to determine the role of political-themed memes on social media in criticizing political policies in the United States (US) in 2016–2019. This period was beginning with the 2016 US presidential election and continuing through Donald Trump's presidency. The use of memes has become a popular medium for expressing US public opinion on policies and political issues that occur in the US. Expression of opinion in the form of praise, support, or criticism was channelled through memes that are created and disseminated on social media. The method used was qualitative, with data sources from books, journals, and official US media. Findings - this study describes memes as an alternative means of representing US public opinion in a light and interesting way. However, the use of memes can only be used as a form of taking a stance on the development of political situations and policies through social media. Novelty - Political instruments that have developed in the midst of digital technology have been an important factor in political discourse in a country. This can provide input for the government and policy makers to take into account the development of discourse on digital media as a form of public participation.